2000
DOI: 10.2308/0148-4184.27.2.177
|View full text |Cite
|
Sign up to set email alerts
|

Publishing Patterns in Specialist Accounting History Journals in the English Language, 1996–1999

Abstract: While accounting researchers have explored international publishing patterns in the accounting literature generally, little is known about recent contributions to the specialist international accounting history journals. Specifically, this study surveys publishing patterns in the three specialist, internationally refereed, accounting history journals in the English language during the period 1996 to 1999. The survey covers 149 contributions in total and provides empirical evidence on the location of their auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
137
2
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(150 citation statements)
references
References 11 publications
10
137
2
1
Order By: Relevance
“…For example, in a recent study, Carnegie and Potter (2000) examined all papers published in specialist accounting history journals in the English language (i.e., Accounting, Business and Financial History; The Accounting Historians Journal; and Accounting History) during the period 1996-1999. Their results revealed that 84.78% of all papers included in their database (149) were authored by scholars affiliated to Anglo-Saxon institutions, whereas France lead the non-Anglo-Saxon counterparts by sharing 8.05% of total contributions.…”
Section: Everybody Knows That …mentioning
confidence: 99%
“…For example, in a recent study, Carnegie and Potter (2000) examined all papers published in specialist accounting history journals in the English language (i.e., Accounting, Business and Financial History; The Accounting Historians Journal; and Accounting History) during the period 1996-1999. Their results revealed that 84.78% of all papers included in their database (149) were authored by scholars affiliated to Anglo-Saxon institutions, whereas France lead the non-Anglo-Saxon counterparts by sharing 8.05% of total contributions.…”
Section: Everybody Knows That …mentioning
confidence: 99%
“…Research into gender diversity and internationalisation of accounting boards has attracted limited attention (exceptions Carnegie et al, 2003 andJones 2008). This contrasts with research into management journal boards, for example, where board characteristics have been extensively examined (Svensson, Slatten and Tronveil 2007;Ozbilgin 2004;Harzing 2009, 2012;Murphy and Zhu 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover I have also considered some relevant papers and articles such as the ones by Garry D. Carnegie and B. N. Potter (2000), Garry D. Carnegie and C. J. Napier (2002), Salvador Carmona (2003), Richard K. Fleischman and Vaughan S. Radcliffe (2005) as well as the subsequent discussion carried on it by Garry D. Carnegie (2006) and Vaughan S. Radcliffe (2006), and finally the paper by Stephen P. Walker (2005).…”
Section: Introduction: Scope Methodology Sources and Limitationsmentioning
confidence: 99%